Seed Culture of Phaius tankervilliae Bl. - Bhuyan, J.; Deka, P. C. (Indian Forester, 1999)
Nitsch and Nitsch (1969) medium was found to be the most suitable medium for the germination of seeds of Phaius tankervilliae Bl., an endangered orchid species of N.E. India. Good germination (70%) was observed when 170 days old seeds of this orchid were cultured in this medium. Germination could be further enhanced by growing the seeds in the same medium supplemented with coconut water or pineapple juice (20 mlll). Addition of banana extract (20 ml/L) in the medium resulted better growth and development of the seedling after germination.